Adsorção e dessorção de selênio em solos cultivados e não cultivados sob Cerrado - Lessa, Josimar Henrique de Lima (2015)
Selenium (Se) is a non-metal element occuring associated with organic and inorganic materials, being considered essential to human and animal life. The Se content in human depends on the factors, such as the quantity and mobility of this element in the soil. Aiming to assess selenium (Se) adsorption and desorption in cultivated and uncultivated soils under Cerrado, it was performed an experiment using 5 soils with different textures and cultivation time. The adsorption test was conducted adding Se from 0 to 2000 μg L-1, as sodium selenate, and using 0,015 mol L-1 of sodium clorite as eletrolyte solution. The solution pH was adjusted to 5.5 and the reaction time for the adsorption was 72 h, alternating 12 h of shaking and 12 h of resting. In desorption, it was added only the NaCl solution to realese the Se previously adsorbed. The data were fitted to Langmuir and Freundlich isotherms, being all soils well fitted to the Freundlich than Langmuir. Through the Langmuir model, it was estimated the maximum Se adsorption capacity (MAC) for all soils evaluated. The soil management, clay, and phosphorus contents, pH as well as the cultivation time had effect on the sortive behavior of the soils. The native soils adsorbed more Se than the cultivated ones, which were attributed to the presence of other anions on part of the adsorption sites in the cultivated soils. The desorption of Se increased upon increasing the amount of this element added. Using the distribution coefficient (Kd), it was evaluated the Se-soils affinities, which have demostrated to be higher for the native soils.